PEMBERDAYAAN UMKM MELALUI KOMUNIKASI DAN INFORMASI PADA PELAKU USAHA DI KELURAHAN PEDURUNGAN TENGAH SEMARANG - Harminingtyas, Rudika; Widowati, Maduretno; Wahyuningsih, Panca (Fokus ABDIMAS, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the local economy, serving as a solution to unemployment. Remarkably, they manage to survive in various economic conditions. However, many operate solely based on business instincts and do not consider the evolving business landscape. Therefore, it is essential to provide information through communication and education. This is especially relevant for MSME entrepreneurs in the Pedurungan Tengah neighborhood in Semarang, particularly those in the culinary/food industry. Outreach efforts should focus on communicating and delivering the latest information, especially regarding online marketing, both in terms of sales and promotions. Keyword : Counseling, Communication, and Information